Citric Acid Fermentation by Locally Isolated Aspergillus Niger M2sg1-Ms4 - Mohd Noor, Noorollhamezon (2004)

(untitled)
The citric acid fermentation by locally isolated strain of Aspergillus niger was carried out using shake flask culture and 2 L stirred tank fermenter. The pure strain was obtained through monospores isolation step using spread plate technique. From morphological and biochemical properties, isolated monospore M2sgl -MS4 can be suggested belong to the strain Aspergillus species. Optimization of fermentation medium for citric acid production by the locally isolated A. niger M2Sgl-MS4 was achieved using 200 g/L of glucose and 0.8 g/L of ammonium nitrate. Addition of 3% (vfv) methanol to the optimized medium improved citric acid production (62.5 glL) by about two times higher compared to control. Trace elements used were similar to the trace elements used in a fermentation medium described by Osthman et al. (1 999). Optimum fermentation condition for citric acid production by M2sgl-MS4 was obtained at initial pH range between 2.5-3.0, temperature of 30°C and agitation speed of 1000 rpm with 1.0 vvm airflow rate. Maximum citric acid concentration obtained under this condition was approximately 62.5 g/L, which gave the yield and overall productivity of 0.41 glg and 0.19 g/L/h, respectively. Foaming is one of the problems normally encountered in submerged fermentation using bioreactor as a result of bubble aeration. In order to find approach for minimizing foam formation during citric acid fermentation in stirred tank fermenter, the effect of several fermenter configurations based on number of impeller and baffles used on foam formation tested. The fermenter with 4-baffles and a single Rushton turbine impeller was found suitable to avoid excessive foaming during the fermentation. The development of dissolved oxygen tension (DOT) control strategies aimed at improving citric acid production in 2 L stirred tank fermenter was also carried out. Maximum citric acid production was obtained in batch fermentation in which DOT was controlled at 80% saturation through out the fermentation. Approximately, 69.06 g/L citric acid which gave yield and overall productivity of 0.47 g/g and 0.22 g/L/h respectively was obtained after 3 12 h of fermentation. This result indicates that the high DOT was needed for high glucose conversion to citric acid throughout the fermentation process.